2016
DOI: 10.1097/qad.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Treatment interruption in chronically HIV-infected patients with an ultralow HIV reservoir

Abstract: In a highly selected population of 10 patients with chronic HIV infection, an excellent immune status, durable virological suppression and ultralow reservoir, the success rate of ATI was 10% (95% confidence interval 0.3-44.5%) and nine of 10 patients had prompt rebound of plasma viremia. Resumption of ART led to return to baseline cell-associated total DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
63
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 24 publications
8
63
2
Order By: Relevance
“…1g–h) (12). In all cases, HIV rebound was observed by 2 weeks after therapy interruption, a time to rebound that is within the range observed for patients (18). Considering the absence of detectable viral RNA and DNA in macrophages isolated from ART-suppressed BLT mice, the rapid rebound observed ostensibly results from virus present in T cells.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…1g–h) (12). In all cases, HIV rebound was observed by 2 weeks after therapy interruption, a time to rebound that is within the range observed for patients (18). Considering the absence of detectable viral RNA and DNA in macrophages isolated from ART-suppressed BLT mice, the rapid rebound observed ostensibly results from virus present in T cells.…”
supporting
confidence: 80%
“…indicate that reductions of 2–3 logs in the number of latently infected cells are needed to delay rebound for the time reported herein for MoM (29). The delay in rebound observed in MoM is greater than that reported for patients initiating ART during the chronic phase of infection (30) and from patients with an ultralow HIV reservoir (18). Our results indicate that HIV-infected tissue macrophages have a short half-life and that ART alone can significantly reduce the levels of infected tissue macrophages, further demonstrating the critical contribution of T cells to the viral reservoir.…”
mentioning
confidence: 62%
“…Conversely, a TI study comparing initiation of ART during early infection versus CHI found an 8.3% rate of post treatment control at 48 weeks among those who started ART during early infection and no post-treatment control among those who started ART during CHI 7 . Even in a highly preselected group of individuals (based on low cell-associated DNA) who initiated therapy in chronic infection and underwent a TI the rates of PTC were 10% 14 . In a retrospective cohort study of individuals started on ART during CHI, 1.6% of individuals were reported to be PTCs 15 .…”
Section: Introductionmentioning
confidence: 97%
“…The presence of PTCs has been examined in both prospective treatment-interruption (TI) and retrospective cohort studies 215 . Reported rates of post treatment control are variable and have ranged from the absence of the phenotype 26 to rates ranging from 4–14% 714 . This variation is partially explained by differences in baseline characteristics of the populations and the definitions of post treatment control in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other few reported cases of long-term remission in individuals controlling viral replication after ART interruption, also called “post-treatment controllers”, have been documented (913). However for most HIV-infected individuals, HIV viral load rebounds at a median time of 14 days after treatment interruption from a large number of HIV variants (1416). Inducing HIV expression has been proposed as a strategy to eliminate persistently HIV-infected cells that constitute the viral reservoir (1719).…”
Section: Introductionmentioning
confidence: 99%